Promoting teachers' agency: reflective practice as transformative disposition. Issue 2 (4th March 2018) - Kramer, Martin
Abstract: Reflective practice has been criticised for having become a standardised method in teacher education and on-the-job training, oftentimes following routines that more likely turn out to be self-affirming than to actually foster change. Also, reflective practice is still widely understood as an individual process. Both aspects are considered problematic and are addressed by employing an activity-theoretical approach that is suggested to be essentially compatible with an existentialist perspective on reflective practice as offered by Thompson and Pascal. Utilising the theory of expansive learning, formative interventionist methodology is proposed to provide a robust framework for developing collaborative and critical reflective practice, which in turn reveals the transformative potential of teachers' agency, as illustrated by a study accompanying and supporting the development of an Austrian secondary school.